Relationship satisfaction and concordance in attitudes to maternal employment in British couples with young children. (July 2020) - Bird, Lauren; Sacker, Amanda; McMunn, Anne
Changes in paid labor in families have occurred within the wider context of societal changes in gendered attitudes to work. However, changes in behavior and attitudes are not necessarily correlated with each other, and their associations with family relationships are complex. This study uses data from over 12, 000 two-parent families in the U.K.'s Millennium Cohort Study, a nationally representative cohort of children born during 2000–2002. The study investigates the potential association between relationship satisfaction and discordance between attitudes to maternal employment and mothers' actual participation in paid labor, as well as agreement in attitudes within couples. Results show that attitudes in favor of maternal employment and actual maternal employment are generally associated with better relationship satisfaction for both mothers and fathers. In addition, discordance between an individual's attitudes and behavior in relation to maternal employment, and discordant attitudes within couples, is both associated with significantly lower relationship satisfaction compared with concordant couples.